Modeling Portable Manager Aiding in the MANET Communication - Ganesh Kumar; A. Arivazhagan (Institute of Advanced Engineering and Science, 2018)
The aim of this paper is to model the Portable Manager and allow it to aid in communication among Mobile Ad-hoc Networks (MANETs) carrying information across the mobile nodes in the network. In this article, Modeling Portable Manager aiding in the MANET Communication (MMAC) is proposed. The novelty is present in the use of node performance parameter called as α defined as the ratio of the packet received, packet loss and delay of the node which could be used for the next hop selection in the mobile ad hoc network. The Portable Manager (PM) is used to find out the relay node in the network. The working of the PM with a minimal number of nodes is analyzed and presented through the simulations in the network simulator.